Physicochemical And Phytotoxicity Analysis Of Sago Bark Waste Compost - Rafeah, Wahi; Effa Radika, Bidin; Zainab, Ngaini (2018)
Sago bark (SB) waste is available abundantly as sago processing by-products in Sarawak. The release of SB waste into waterways could harm aquatic life and burning of SB will cause air pollution. In this work, SB waste is utilized via composting process to produce compost foragricultural use.The physicochemical characteristics and phytotoxicityof the prepared compost was evaluated monthly. SB compost was prepared by mixing SBwaste with chicken manure and empty fruit brunch (EFB) in ratio 6:6:1. The maturity and stability of compost in three months composting process was evaluated via physicochemical characterization of the composts in terms of pH, total ash content, total organic content and elemental analysis. The effect of the composts usage as growth medium and the phytotoxicitywas assessed towards aromatic lettuce via seed germination. Results showed that after three months, the composts colour were dark brown with earthy smell. The volume and weight of the compost was decreased.The total ash content and total organic matter of the SB compost were increased and decreased respectively during 3 months composting. Total C/N ratio was 21.63, 13.38 and 4.91 during first, second and third month respectively. The pH of the compost is alkaline after three months of composting. The germination index (GI) for studied vegetables was >100% after five days after germination.